Opportunities for Non-Hormonal Treatment of Breast Benign Dysplasia - M.R, Orazov; E.N, Nosenko; L.V, Pokul; L.R, Toktar; O.S, Sakultsan; A.V, Rutinskaya; A.N, Akhmatova (International Journal of Psychosocial Rehabilitation, 2020)
Benign breast dysplasia (BBD) is widespread in the female population and is one of the most important risk factors for breast cancer. The use of ultra-diluted natural products in the treatment of diseases and in the treatment of hyper proliferative processes and cancer causes great interest and controversies. The aim of the study was to investigate the effectiveness and safety of the non-hormonal drug Mastopol® in the treatment of various forms of BBD in women of reproductive age.